Analisis Ketimpangan Keadilan di Indonesia: Potret Buram Hukum yang Berpihak pada Kuasa - Nurrahim Hasan Al Banna; Naufal Nafis Ardana; Muhammad Fakhri Kurniawan; Ramadhan Dwi Prasetyo (Badan Pembinaan Ideologi Pancasila, 2025)
This study aims to analyze the factors causing inequality in access to justice between upper and lower groups in the Indonesian legal system and its impact on public trust and social structure. This study uses a normative legal research method with several approaches, namely: (1) A conceptual approach to analyze the concept of justice, inequality, and human rights in the context of national and international law; (2) A legislative approach to analyze legal provisions related to the right to justice and legal aid; (3) A sociological approach to analyze the impact of inequality in access to justice based on empirical data. The results of the study indicate that inequality in access to justice is caused by socio-economic factors, low legal literacy, and the dominance of power in the legal system. The impact is a decrease in public trust in the legal system, widening social disparities, and strengthening structural discrimination. Based on these findings, the study recommends strengthening legal aid institutions, increasing public legal literacy, and reforming the legal system by emphasizing transparency and accountability, as well as the use of information technology to create more equal and inclusive access to justice.